Pengaruh Media Pembelajaran Smartbox Berbasis QR Code terhadap Minat Belajar IPAS Siswa Kelas IV - Bella, Zahra Salsa; Noperman, Feri; Yusnia (JURIDIKDAS, 2025)
This study aims to determine the effect of Smartbox learning media based on QR Code on the learning interest of fourth-grade students in the IPAS subject at SD Negeri Gading Cempaka District, Bengkulu City. The research uses a quantitative approach with a quasi-experimental method. The design applied is The Matching Only Pretest-Posttest Control Group Design. The population in this study consisted of fourth-grade students from SD Negeri Gading Cempaka District, a school with A accreditation, implementing the Merdeka curriculum, and supported by adequate technology such as Chromebooks, projectors, and WiFi networks. Sampling used the Cluster Random Sampling technique. The selected experimental group was class Four A at SDN 05 Bengkulu City, and the control group was class Four B at SDN 24 Bengkulu City. The tool used for both the pretest and posttest was a 10-statement questionnaire. Methods for analyzing the data included t-test inferential analysis, precondition tests, and descriptive statistics. The experimental group outperformed the control group on average after the intervention, with a posttest score of 40.34 compared to 35.38. H₀ is rejected and Ha is approved since the t-test results demonstrated a significance value of 0.002 < 0.05. Therefore, Smartbox media that utilizes QR codes has a beneficial impact on students' motivation to study.